2016
DOI: 10.1161/circimaging.115.003866
|View full text |Cite
|
Sign up to set email alerts
|

Sex- and Method-Specific Reference Values for Right Ventricular Strain by 2-Dimensional Speckle-Tracking Echocardiography

Abstract: Accordingly, in this prospective study, we aimed to (1) assess the presence and extent of measurement variability in relation to the various methods and definitions of RVLS, Background-Despite the fact that assessment of right ventricular longitudinal strain (RVLS) carries important implications for patient diagnosis, prognosis, and treatment, its implementation in clinical settings has been hampered by the limited reference values and the lack of uniformity in software, method, and definition used for measuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
129
4
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 188 publications
(162 citation statements)
references
References 31 publications
14
129
4
8
Order By: Relevance
“…5 In our single-center validation cohort, LA 3DE volume measurements were tightly correlated and slightly underestimated in comparison with CMR, in line with other validation studies comparing 3DE volumes of LV and RV with CMR. 23,24 The bias was significantly larger in patients with enlarged atria (Figure 4). Our limits of agreement with CMR are similar those reported by Mor-Avi et al, 5 whereas the systematic bias is larger (−8 versus −1 mL).…”
Section: Reference Values For La Volumesmentioning
confidence: 92%
“…5 In our single-center validation cohort, LA 3DE volume measurements were tightly correlated and slightly underestimated in comparison with CMR, in line with other validation studies comparing 3DE volumes of LV and RV with CMR. 23,24 The bias was significantly larger in patients with enlarged atria (Figure 4). Our limits of agreement with CMR are similar those reported by Mor-Avi et al, 5 whereas the systematic bias is larger (−8 versus −1 mL).…”
Section: Reference Values For La Volumesmentioning
confidence: 92%
“…The largest study providing sex-and methodspecific reference values for RVLS was conducted in 276 healthy volunteers by Muraru et al [53]. Reference values (lower limits of normality) were as follows: (i) six-segment RVLS, -24.7 ± 2.6% (-20.0%) for men and -26.7 ± 3.1% (-20.3%) for women; (ii) free wall (three-segment) RVLS, -29.3 ± 3.4% (-22.5%) for men and -31.6 ± 4.0% (-23.3%) for women.…”
Section: Right Ventricular Strain and Strain Rate By 2d Speckle Trackingmentioning
confidence: 99%
“…Muraru et al [53] also demonstrated that free wall RVLS from a six-segment region of interest was more feasible and reproducible than from a three-segment one.…”
Section: Right Ventricular Strain and Strain Rate By 2d Speckle Trackingmentioning
confidence: 99%
“…In healthy subjects, left ventricular longitudinal strain and right atrial longitudinal strain were identified as correlates of RV longitudinal strain, suggesting the capability of 2DSTE to evaluate the functional coupling of the RV with the left ventricle or right atrium. 5 It would be extremely interesting to verify if the same relationships occur also in systemic conditions such as SSc, known to potentially affect both RV and left ventricular myocardium.…”
Section: See Article By Mukherjee Et Almentioning
confidence: 99%
“…The RVFWLS values reported by Mukherjee et al 3 in their control subjects are significantly lower than those reported in the literature. 5,9 However, they used a novel vendor-independent software package (EchoInsight, Epsilon Imaging, Ann Arbor, MI) to measure RVFWLS, whereas the large majority of investigators who applied RVFWLS for RV analysis used a different software (EchoPac, GE Vingmed, Horten, Norway). 2,5,9 In addition, technical details such as the acquisition of the RV view (standard apical 4-chamber versus RV-focused apical 4-chamber view) and the way RV longitudinal strain is defined and calculated (ie, including or not including the interventricular septum) may significantly affect its values.…”
Section: See Article By Mukherjee Et Almentioning
confidence: 99%